Pengaruh Kemiringan Benda Kerja dan Kecepatan Pemakanan terhadapGetaran Mesin Frais Universal Knuth UFM 2 - Romiyadi Romiyadi (JURNAL MECHANICAL, 2016)
In milling process with slope of workpiece, the milling process requires more energy from milling machine. The greater the slope of workpiece estimated to be the greater energyrequired by the milling machine. Therefore, the machining vibration that occurs was estimated to be very big. This study aimed to determine influence theslope of workpiece to machining vibration in milling machine with variations of feeding. This study used Milling Machine Knuth Universal UFM 2 with vertical milling approach. The slope of workpiece used was 300, 450 and 600.The machining process parameters varied was feeding while depth of cut and spindle speed were constant. The study results show that the greater the slope of work piece, the greater the machining vibration on the up milling process and the down milling processes for all slope of work piece. Similarly the influence of feeding to machining vibration in milling process. The study results show that the change of feeding will give a positive impact to machining vibration on the up milling process and the down milling processes. For same the slope of workpiece and feeding the machining vibration on the down milling process is greater than the up milling process.